PENGARUH EKSEKUTIF WANITA, STRUKTUR MODAL, DAN PERTUMBUHAN LABA TERHADAP FINANCIAL DISTRESS - Purwaningsih, Eny; Zelina, Riza (Universitas Trilogi, 2023)
The purpose of this study is to find out empirically about the influence of female executives, capital structure, and profit growth on financial distress either partially or simultaneously in retail sub-sector companies listed on the Indonesia Stock Exchange in the 2015-2019 period. This research uses causal-comparative research which is used to determine the causal relationship between two or more variables. The sample in this study is retail companies listed on the Indonesia Stock Exchange for the 2015-2019 period using the purposive sampling method. There are 10 companies that meet the criteria of the research sample, so the sample is 50 financial statements. The results showed that partially there was a capital structure variable (debt to equity ratio) that had a negative effect on financial distress, profit growth variables had a negative effect on financial distress, and female executives had no effect on financial distress.Keywords: Female Executives, Capital Structure, Profit Growth, Financial Distress